1992
DOI: 10.1007/bf00230388
|View full text |Cite
|
Sign up to set email alerts
|

Functional topography of cat primary auditory cortex: representation of tone intensity

Abstract: The neuronal response to tones as a function of intensity was topographically studied with multiple-unit recordings in the primary auditory cortex (AI) of barbiturate-anesthetized cats. The spatial distribution of the characteristics of rate/level functions was determined in each of three intensely studied cases and their relationship to the distribution of spectral parameters (sharpness of tuning and responses to broadband transients) in the same animals was determined. The growth of the high-intensity portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 43 publications
6
76
0
1
Order By: Relevance
“…Although this is a possibility, multiple considerations argue against N1 enhancement as an explanation for the current set of results. First, results of animal studies indicate that at the suprathreshold intensities used in the current study, the firing rates of neurons change very little in response to intensity level if they have monotonic rate intensity functions, and can even decrease for those cells that have nonmonotonic intensity functions (e.g., Schreiner et al, 1992). Moreover, in humans, at the intensity and frequency levels used in the current study, only a minimal difference in N1 amplitude has been reported (Biermann and Heil, 2000;Schröger, 1994).…”
Section: Discussionmentioning
confidence: 79%
“…Although this is a possibility, multiple considerations argue against N1 enhancement as an explanation for the current set of results. First, results of animal studies indicate that at the suprathreshold intensities used in the current study, the firing rates of neurons change very little in response to intensity level if they have monotonic rate intensity functions, and can even decrease for those cells that have nonmonotonic intensity functions (e.g., Schreiner et al, 1992). Moreover, in humans, at the intensity and frequency levels used in the current study, only a minimal difference in N1 amplitude has been reported (Biermann and Heil, 2000;Schröger, 1994).…”
Section: Discussionmentioning
confidence: 79%
“…At each site, the spontaneous firing rate collected during the 100 ms before stimulus onset was subtracted from the stimulus onset response (mean duration of the onset response Ϯ SD, 21.44 Ϯ 10.68 ms). Each RLF was normalized to its maximum firing rate, and the following measures (defined below) were derived according to the method outlined by Schreiner et al (1992): (1) minimum response threshold; (2) transition point; (3) best level; (4) slope of the RLF between the minimum response threshold and the transition point; and (5) monotonicity. If the spike rate remained at zero for two consecutive sound levels, all sound levels less than or equal to the greater of the two levels were considered subthreshold.…”
Section: Methodsmentioning
confidence: 99%
“…The first tonotopic auditory neocortical map was demonstrated by Woolsey and Walzl (1942) in the form of a cochleotopic organization in the primary auditory cortex (AI) of the cat. Other functional maps in AI include binaural interaction bands (Imig and Adrian, 1977;Middlebrooks et al, 1980), threshold/intensity (Tunturi, 1950;Schreiner et al, 1992), and sharpness of tuning (Schreiner and Mendelson, 1990). Interestingly, these maps are patchy or discontinuous in their distribution relative to the frequency map Brugge and Imig, 1978;Middlebrooks et al, 1980;Reale and Imig, 1980;Redies et al, 1989;Schreiner, 1991Schreiner, , 1992Schreiner et al, 1992Schreiner et al, , 2000Mendelson et al, 1993Mendelson et al, , 1997Fitzpatrick et al, 1998).…”
Section: Introductionmentioning
confidence: 99%